2010
DOI: 10.1534/genetics.110.116665
|View full text |Cite
|
Sign up to set email alerts
|

Stb3 Plays a Role in the Glucose-Induced Transition from Quiescence to Growth inSaccharomyces cerevisiae

Abstract: Addition of glucose to quiescent Saccharomyces cerevisiae cells causes the immediate induction of $1000 genes. These genes include ribosomal proteins (RP) and non-RP genes needed for ribosome production and other growth processes. RRPE sequence elements are commonly found 59 of non-RP growth gene ORFs, and Stb3 has recently been identified as an RRPE binding protein. Stb3 overexpression (Stb3OE) produces a slow growth phenotype that is associated with reduced expression of non-RP genes and a drop in the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 64 publications
3
47
0
Order By: Relevance
“…Our results are consistent with the independent finding that the binding of Stb3 to the RRPE-containing NSR1 and DBP10 promoters is increased in response to glucose replenishment and that an stb3⌬ strain fails to increase the expression of RRB genes during this environmental change (23). However, a more recent investigation by the same group indicated that Stb3 may also be acting as a repressor, as overexpression of STB3 results in decreased expression of growthrelated genes, and this is alleviated by deletion of the HOS2 histone deacetylase (22). In fact, these seemingly contradictory roles are both consistent with our observations that the RRPE sequence is involved in both transcriptional activation and repression of the same genes under different circumstances.…”
Section: Discussionmentioning
confidence: 92%
“…Our results are consistent with the independent finding that the binding of Stb3 to the RRPE-containing NSR1 and DBP10 promoters is increased in response to glucose replenishment and that an stb3⌬ strain fails to increase the expression of RRB genes during this environmental change (23). However, a more recent investigation by the same group indicated that Stb3 may also be acting as a repressor, as overexpression of STB3 results in decreased expression of growthrelated genes, and this is alleviated by deletion of the HOS2 histone deacetylase (22). In fact, these seemingly contradictory roles are both consistent with our observations that the RRPE sequence is involved in both transcriptional activation and repression of the same genes under different circumstances.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, TORC1 and PKA inactivate repressors of ribi genes such as Dot6p and Tod6p (Huber et al, 2011; Lippman and Broach, 2009). Stb3p, a repressor of rRNA processing genes, is also inactivated by TORC1 and glucose (Huber et al, 2011; Liko et al, 2010). We show that Ifh1p is yet another ribosomal transcription factor that is exposed to phosphorylation by TORC1 and PKA signaling.…”
Section: Discussionmentioning
confidence: 99%
“…First, we identified classes of nucleosomes that were found in the same promoters as a given cis-regulatory element more often than would have been expected by chance. Several classes of nucleosome gain were associated with PAC elements and ribosomal RNA-processing elements (RRPEs), which repress protein syn- thesis genes upon stress (6,41,46,48,82), and Rap1p sites that regulate RP genes (44). Nucleosomes depleted with different dynamics were found in association with several stress-activated transcription factors: all classes of nucleosome depletion were found within promoters containing the related Msn2p and Mig1p binding sites ([CCCCT] and [GCCCCV], respectively), while specific classes were found associated with Pdr3p, Yap1p, and Rpn4p binding sites at genes involved in redox response, oxidative stress, and proteasome expression, respectively.…”
Section: [T Tests])mentioning
confidence: 99%